Dual regulation of the cGAS-STING pathway: new targets and challenges for subtype-specific immunotherapy in breast cancer - Xiong, Hanchu; Li, Rongxue; Yang, Lixian; Li, Yucheng; Ma, Xiao (Frontiers in Oncology, 2025)
Research on immune regulation mechanisms in breast cancer is crucial for breaking through therapeutic bottlenecks. This paper comprehensively reviews the dual roles of the cGAS-STING pathway in Luminal, HER2+, and triple-negative breast cancer (TNBC): its activation can enhance antitumor immunity, but chronic activation may lead to immunosuppression. By integrating molecular mechanisms, clinical translation, and subtype-specific strategies, it provides new directions for precision immunotherapy.